Current state of female pediatric urologists at Societies for Pediatric Urology fellowship accredited programs - Armon, Natalie; Thompson, Nora; DaJusta, Daniel; Fuchs, Molly; Ching, Christina B. (Frontiers in Urology, 2023)
Purpose: Gender inequities in medicine exist. Urology is a male dominated surgical specialty, with recent census data showing females represent only 10.9% of the workforce. We aimed to characterize the composition of female pediatric urologists across the Societies for Pediatric Urology (SPU) pediatric urology fellowship accredited programs, with particular attention to academic promotion and leadership positions. Methods: In January 2023, we reviewed the official websites of the 27 pediatric urology programs listed on the SPU website as fellowship accredited programs. We identified pediatric urology surgery attendings, their gender, academic title, and if they were named a director of an internal program or had a hospital leadership position. We identified the program chief and fellow/resident program director. This data was associated with years in practice. Results: Females represented 27.4% of pediatric urology surgical attendings. Four programs (14.8%) had no female attendings. Female staff were in practice a median shorter time than that of males (6 vs. 16 years, p<0.0001). A significantly higher proportion of females were assistant professors (62.2 vs. 35.2%; p=0.0041) while a significantly higher proportion of men were professors (37.0 vs. 18.9%; p=0.0421). Only one program (3.7%) had a female department/division chief. There was no difference between genders regarding being named a director of a program and/or having an identified hospital position of leadership. Female professors had been in practice a significantly shorter time than male professors (p=0.0003); women with an internal or hospital leadership position had also been in practice a significantly shorter time than males (p<0.001). Conclusions: Females are represented more in SPU pediatric urology fellowship accredited programs than the overall urology workforce. Fewer female attendings are professors compared to male attendings; however, differences in promotion could be impacted by female attendings being earlier in their career. Hopefully with time, we will see more equal representation amongst genders in pediatric urology programs overall, but especially where we are training the next generation.